A weaker, Cheaper MRI. - Savage, N.
The first images of a human brain using magnetic fields a hundred-thousandth the strength of conventional magnetic resonance imaging (MRI), paving the way for lower cost medical images that might be better at detecting tumors. To detect the weaker signals, an array of seven supersensitive magnetometers called superconducting quantum interference devices, or SQUIDs is used.
Keywords: SQUID; Cheaper MRI; Human brain; Low-field MRI; Magnetic fields; Magnetic resonance imaging; Superconducting quantum interference devices; Supersensitive magnetometers arrays; Tumors detection